If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -3)(m + 7) = 3x Reorder the terms: (-3 + 4x)(m + 7) = 3x Reorder the terms: (-3 + 4x)(7 + m) = 3x Multiply (-3 + 4x) * (7 + m) (-3(7 + m) + 4x * (7 + m)) = 3x ((7 * -3 + m * -3) + 4x * (7 + m)) = 3x ((-21 + -3m) + 4x * (7 + m)) = 3x (-21 + -3m + (7 * 4x + m * 4x)) = 3x Reorder the terms: (-21 + -3m + (4mx + 28x)) = 3x (-21 + -3m + (4mx + 28x)) = 3x (-21 + -3m + 4mx + 28x) = 3x Solving -21 + -3m + 4mx + 28x = 3x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '21' to each side of the equation. -21 + -3m + 4mx + 21 + 28x = 21 + 3x Reorder the terms: -21 + 21 + -3m + 4mx + 28x = 21 + 3x Combine like terms: -21 + 21 = 0 0 + -3m + 4mx + 28x = 21 + 3x -3m + 4mx + 28x = 21 + 3x Add '-28x' to each side of the equation. -3m + 4mx + 28x + -28x = 21 + 3x + -28x Combine like terms: 28x + -28x = 0 -3m + 4mx + 0 = 21 + 3x + -28x -3m + 4mx = 21 + 3x + -28x Combine like terms: 3x + -28x = -25x -3m + 4mx = 21 + -25x Reorder the terms: -21 + -3m + 4mx + 25x = 21 + -25x + -21 + 25x Reorder the terms: -21 + -3m + 4mx + 25x = 21 + -21 + -25x + 25x Combine like terms: 21 + -21 = 0 -21 + -3m + 4mx + 25x = 0 + -25x + 25x -21 + -3m + 4mx + 25x = -25x + 25x Combine like terms: -25x + 25x = 0 -21 + -3m + 4mx + 25x = 0 The solution to this equation could not be determined.
| 0=x^2-6x-16 | | 18v-9v=54 | | .5(8y-2)=16-30y | | 32=-5-3t | | Z^4-9z^2=0 | | 3x+9y+10y+2=180 | | 13-(2x+2)=2(2+x)3x | | 1=2d-1 | | 4(3y-8)-11y=2 | | 5s+3=12 | | 2x+7=-8-3x | | 5+4t-(3t+4)-(4t+4)= | | 0.8-6=0.6a+22 | | 8m-11=3(2m+7) | | -4(z-3)=2-3x | | 3(4x+1)=15 | | 2x+xy+2y=0 | | .5x+.4x=16 | | 1+y/5=1 | | 3a+-2=-5 | | -14=5y-2(y+1) | | -7(-2+4x)=14+x | | -11=2.5d | | 2(3w-6z+7wz)-8(2w+z+3wz)= | | 1/4+1/5=x | | 3+-5x=3 | | 5x-7(-2x-11)=-18 | | 13=5-(x+1) | | -8=-1.6s | | 6t-2-t=16 | | -8=-1.6 | | 14.2y-25.2=3.8y+26.8 |